The clinical-epidemiological profile of the elderly with bronch cancer and lung in Pará between 2014-2018 (Research, Society and Development, 2021)
Objective: Bronchial and lung cancer (CP) is a highly lethal disease. It is usually detected in advanced stages, since the symptoms of the disease are not detected in the early stages. The elderly population for having longer exposure to factors such as consumption of tobacco derivatives, becoming more susceptible to this type of cancer. To identify the clinical-epidemiological profile of the elderly with Bronchial and Lung Cancer in Pará between the years 2014 to 2018. Methodology: This is an exploratory and quantitative study, with a descriptive design. The research was carried out in August 2020, with information available in the Hospital Cancer Registry Computerization System (SisRHC) regarding mortality from lung and bronchial cancer in the state of Pará in the period from 2014 to 2018. Results: It was found the total of 461 cases of bronchial and lung cancer in the state of Pará between 2014 to 2018, with a predominance of the age group from 60 to 69 years old, male, mixed race, incomplete elementary level and married marital status, it was observed that 287 (62%) were ex-consumers. In relation to alcoholism, it was found that in 192 (42%) of the cases did not have information or there was no evaluation and 262 (57%) of the cases did not present information about the family history of cancer. Conclusion: It was found that smoking is the main influence to develop and increase cases of bronchial and lung cancer, even with a national tobacco control program, offered by the Ministry of Health, it has a relevant resistance by users.